Probiotic supplementation modifies the gut microbiota profile of very low birth weight preterm infants during hospitalization - Hung-Yang Chang; Chia-Ying Lin; Jen-Shiu Chiang Chiau; Jui-Hsing Chang; Chyong-Hsin Hsu; Mary Hsin-Ju Ko; Hung-Chang Lee (Elsevier, 2024)
Background: Probiotic supplementation is increasingly being given to very low birth weight (VLBW) preterm infants. This preliminary observational study aimed to investigate the effects of multiple-strain probiotics on the gut microbiota of VLBW preterm infants. Methods: We collected meconium and stool samples on days 14, 30, and 60 after birth from 49 VLBW infants with a gestational age of <32 weeks. The infants were divided into the probiotics (n = 24) and control (n = 25) groups. The microbial composition and diversity in the gut of the two groups were analyzed using 16 S rRNA gene sequencing. Results: The relative abundance of Bifidobacterium and Lactobacillus was significantly higher in the probiotics group than in the control group on days 14, 30, and 60 (Bifidobacterium: p = 0.002, p < 0.0001, and p < 0.0001, respectively; Lactobacillus: p = 0.012, p < 0.0001, and p < 0.0001, respectively). The control group exhibited a significantly higher proportion of participants with a low abundance (<1%) of Bifidobacterium or Lactobacillus on days 14, 30, and 60 than those in the probiotic group. Moreover, the probiotics group exhibited a significantly lower abundance of Klebsiella on days 14 and 30 (2.4% vs. 11.6%, p = 0.037; and 7.9% vs. 16.6%, p = 0.032, respectively) and of Escherichia-Shigella on day 60 than the control group (6.1% vs. 12.3%, p = 0.013). Beta diversity analysis revealed that the microbiota profile was clearly divided into two groups on days 30 and 60 (p = 0.001). Conclusion: Probiotic supplementation significantly increased the relative abundance of Bifidobacterium and Lactobacillus and inhibited the growth of potential pathogens. Furthermore, probiotic supplementation led to a distinct gut microbiota profile. Further research is needed to identify probiotic strains that exert significant influence on the gut microbiome and their long-term health implications in preterm infants.